Penerapan dan Efektivitas Konseling Individual bagi Peserta Didik Terdampak Perceraian Orang Tua - Fauzi; Wira Nita, Rahma; Nora Dwi Putri, Besti (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
The phenomenon of parental divorce is one of the events that can have a significant psychological impact on adolescents, especially high school students. This condition often causes feelings of depression, decreased motivation to learn, and difficulties in adapting to the school environment. This study aims to: (1) Describe how students of SMA N 2 Lubuk Sikaping face the impact of parental divorce, (2) Determine the application of individual counseling in students of SMA N 2 Lubuk Sikaping, and (3) Examine the effectiveness of the application of individual counseling for students who experience the impact of parental divorce. This study uses a qualitative approach with descriptive data. The key informants in the study were one of the students (AJ), as well as three additional informants, namely homeroom teachers (NA), BK teachers (AF), and other students (AZ). Data collection techniques were carried out through interviews, observations, and documentation studies. Data analysis is carried out through three stages, namely data reduction, data presentation, and conclusion drawn. The results of the study show that individual counseling plays an important role in helping students affected by parental divorce. BK teachers and homeroom teachers have worked together to provide emotional support and problem-solving strategies. This effort makes students more enthusiastic about learning, able to adapt, and motivated to achieve educational success